Pengembangan Keterampilan Public Speaking Dan Komunikasi Organisasi Pada Anggota Gerakan Mahasiswa Kristen Indonesia Cabang Denpasar - Cipta Dewi, Ni Nyoman; Mehang Tana, Markus (Jurnal Kajian Ilmu Komunikasi, 2022)
Communication is a necessity for humans to interact with one another. Each individual has a specific purpose in establishing communication with others. By understanding and applying public speaking and organizational communication, organization members can find out how the development of public speaking and organizational communication for members of the Indonesian Christian student movement Denpasar branch. In a study entitled "Development of Public Speaking Skills and organizational communication for members of the Indonesian Christian student movement Denpasar branch" used a qualitative approach. The research design uses case studies because it relies on in-depth analysis in accordance with the reality in the field. The research subjects were organizational administrators and members of the organization with data collection techniques using observation techniques, interview techniques and documentation techniques. The data analysis technique used qualitative descriptive. From the results of interviews conducted with organizational management and organizational members, it was concluded that there were eleven indicators in developing public speaking and organizational communication skills, namely presentations, speeches, master of ceremonies, moderators, processes, messages, networks, mutual need, relationships, environment and uncertainty. So the organization is very supportive and provides space for members of the organization to be able to develop public speaking skills